2005
DOI: 10.1521/scpq.20.1.1.64193
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of Readability Estimates' Predictions of CBM Performance.

Abstract: Researchers investigating the psychometric properties of curriculum-based measures in reading (R-CBM) have typically used readability formulas to create passages of similar difficulty. Despite their efforts, many researchers still find excessive, uncontrolled systematic error (presumably due to passage difficulty) in R-CBM data. This study investigates the validity of eight readability formulas by examining their ability to predict students' words read correctly in a minute (WRCM). The study is based on the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
59
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 66 publications
(63 citation statements)
references
References 25 publications
2
59
2
Order By: Relevance
“…Conversely, with more rigorous purposive selection employed to identify passages of a single difficulty, error variance is expected to diminish. Poncy et al (2005) confirmed this principle using generalizability theory, and Ardoin et al (2005) highlighted it while revealing the inadequacy and unreliability of readability measures. CBM-R publishers go to great lengths to write and choose forms of similar difficulty (e.g., Good & Kaminski, 2002;Howe & Shinn, 2002).…”
Section: Traditional Methods For Developing Parallel Passagesmentioning
confidence: 68%
See 2 more Smart Citations
“…Conversely, with more rigorous purposive selection employed to identify passages of a single difficulty, error variance is expected to diminish. Poncy et al (2005) confirmed this principle using generalizability theory, and Ardoin et al (2005) highlighted it while revealing the inadequacy and unreliability of readability measures. CBM-R publishers go to great lengths to write and choose forms of similar difficulty (e.g., Good & Kaminski, 2002;Howe & Shinn, 2002).…”
Section: Traditional Methods For Developing Parallel Passagesmentioning
confidence: 68%
“…In order to maintain simplicity, as CBM-R was geared toward classroom teachers, this process was considered sufficient for approximating equivalent forms (e.g., Deno, 1985;Deno, Marston, & Tindal, 1986). With their extended use and adaptation, parallelism of passages is now typically improved by (a) increasing the number of passages to choose from, (b) ensuring that passages converge on a specific difficulty level (Hintze & Christ, 2004;Poncy et al, 2005), and (c) using the appropriate screening or selection criteria throughout the passage selection process (Ardoin et al, 2005). Convergence on a single difficulty level is critical to identifying potential reading passages.…”
Section: Traditional Methods For Developing Parallel Passagesmentioning
confidence: 99%
See 1 more Smart Citation
“…Ardoin, Suldo, Witt, Aldrich, & McDonald (2005) investigated the validity of eight reliability formulas as predictors of student's WCPM. The stories were from a reading program used in both third and fourth grade.…”
Section: Problems With Readability Equatingmentioning
confidence: 99%
“…For example, Hintze and Christ (2004) recommended the use of readability formulas, and Shinn (2002) in Best Practices in School Psychology IV recommended that a minimum of 10 R-CBM data points be collected to account for measurement error. More recent studies have suggested that readability formulas fail to adequately control passage difficulty (Ardoin, Suldo, Witt, Aldrich, & McDonald, 2005) and that biweekly data collected across 10 weeks rather than only 5 weeks is needed (Christ, 2006, April). The additional data points ideally result in smaller SEbs (Christ, 2006, April) and also may provide time for intervention effects to generalize to nonintervention materials.…”
mentioning
confidence: 99%